Design and development of model for proton exchange membrane fuel cell - Aher, Ankush Babaji; Patil, Sudhir Madhav; Sutikno, Tole (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Fuel prices are rising, and fossil fuel resources are depleting. This fuel is consumed by conventional fuel vehicles, which contributes to increased greenhouse gas emissions and air pollution. Various vehicle technologies have been introduced in modern times. Among these innovations, fuel cell vehicle technology stands out due to its ease of use, robustness, and simplicity. The primary energy source for this system is hydrogen. Fuel cells use hydrogen to generate electricity through a chemical process that does not involve combustion. The purpose of this paper is to describe the design and development of a simulation model for a fuel cell (proton exchange membrane type) vehicle using mathematical equations and the MATLAB/Simulink R2020a software, taking into account all voltage losses and temperature variations of the proton exchange membrane (PEM) type fuel cell. The designed model is validated in two ways: first by generating V-I characteristics for the designed PEM-type fuel cell, and then by performing a performance test in Simulink using the driving cycle on one of the fuel cell vehicles. The obtained simulated results are nearly identical to the expected results, and the designed PEM-type fuel cell performed well in all real-time driving cycle test conditions.